Pacemaker discomfort induced by the wearing of seat belts. Issue 714 (April 1985) - Wallis, M.; Todd, I.; Aber, C. P.
Abstract : A survey was made of 100 consecutive pacemaker recipients to examine problems they may have experienced with seat belts whilst travelling by car, either as drivers (29 patients) or front seat passengers (50 patients). Twenty-one per cent of the drivers and 30% of the front seat passengers had experienced symptoms, usually of a mild nature. Re-siting of the generator was only necessary in 1 patient and no example of electrode displacement was observed. Suggestions are made as to how this problem might be overcome.